2022
DOI: 10.1126/science.abm1215
|View full text |Cite
|
Sign up to set email alerts
|

Where rivers jump course

Abstract: Rivers can abruptly shift pathways in rare events called avulsions, which cause devastating floods. The controls on avulsion locations are poorly understood as a result of sparse data on such features. We analyzed nearly 50 years of satellite imagery and documented 113 avulsions across the globe that indicate three distinct controls on avulsion location. Avulsions on fans coincide with valley-confinement change, whereas avulsions on deltas are primarily clustered within the backwater zone, indicating a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…These avulsions are situated in the backwater transitional reach, downstream of the gravel‐sand transition and alluvial terraces, and thus likely arise due to autogenic processes, including in‐channel sediment aggradation caused by lowering downstream shear stress and sediment‐transport capacity (Figure 10a; Dong et al., 2016; Nittrouer et al., 2012). Specifically, the median avulsion length scale is 1.40 ±0.70.3 ${\pm }_{0.7}^{0.3}$ of the backwater length scale (Brooke et al., 2022; Dong et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These avulsions are situated in the backwater transitional reach, downstream of the gravel‐sand transition and alluvial terraces, and thus likely arise due to autogenic processes, including in‐channel sediment aggradation caused by lowering downstream shear stress and sediment‐transport capacity (Figure 10a; Dong et al., 2016; Nittrouer et al., 2012). Specifically, the median avulsion length scale is 1.40 ±0.70.3 ${\pm }_{0.7}^{0.3}$ of the backwater length scale (Brooke et al., 2022; Dong et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Decades of imagery from remote sensing campaigns (e.g., NASA Landsat) capture diverse examples of channel mobility (Baki & Gan, 2012; Constantine et al., 2014; Gupta et al., 2013; Loveland & Dwyer, 2012; Schwenk et al., 2017; Sylvester et al., 2019). Channels move gradually through the process of riverbank migration (Einstein, 1926; Hickin & Nanson, 1984) and also in abrupt, periodic events such as cutoffs and avulsions that reroute the course of flow (Brooke et al., 2022; Constantine & Dunne, 2008; Hooke, 2004; Slingerland & Smith, 2004). Furthermore, channels exist across a continuum of different planform morphologies, from single‐thread meandering channels (Figure 1a–1d) to multi‐thread anabranching channels (Figures 1e–1g), which can be further categorized as braided, anastamosing, or wandering (Eaton et al., 2010; Galeazzi et al., 2021; Latrubesse, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…that reroute the course of flow (Brooke et al, 2022;Constantine & Dunne, 2008;Hooke, 2004;Slingerland & Smith, 2004). Furthermore, channels exist across a continuum of different planform morphologies, from single-thread meandering channels (Figure 1a-1d) to multi-thread anabranching channels (Figures 1e-1g), which can be further categorized as braided, anastamosing, or wandering (Eaton et al, 2010;Galeazzi et al, 2021;Latrubesse, 2008).…”
mentioning
confidence: 99%
“…DEMs and topographic maps are often used to calculate ratios between cross-valley and down-valley gradients (Aslan et al, 2005;Phillips, 2009;Sinha et al, 2014). Examples using Landsat imagery: Buehler et al (2011) found decreasing channel widths from 1996 to 2008 downstream of an avulsion node; Rosen and Xu (2013) reported rapid growth of the Atchafalaya-Wax Lake delta due to a potential avulsion of the Atchafalaya River; Lombardo (2016) discovered that 29 out of 41 crevasses along tributaries of the Rio Mamaore led to avulsions; Edmonds et al (2016) demonstrated that avulsion courses are controlled by floodplain topography; Brooke et al (2022) documented 113 avulsions over the past 50 years and indicate three distinct controls on avulsion locations. Other Landsat-based studies include mapping of avulsion styles (i.e., incisional vs. depositional) and floodplain disturbance (Valenza et al, 2020), crevasse splays (Iacobucci et al, 2020), and paleochannels (Weissmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%